Improving mathematical modeling competencies of mathematics teachers in a technology-supported learning environment - Bilgili, Sibel; Çiltaş, Alper (Frontiers in Education, 2025)
Mathematical modeling process has an important role in solving problems encountered in daily life. For this reason, this study aims to improve mathematical modeling competencies of mathematics teachers through training in a learning environment prepared with a mathematical modeling approach. In this case study research, the participants were 5 volunteer mathematics teachers working in public schools. The study was designed with a specific process and firstly, teachers were interviewed and their preliminary information about mathematical modeling was obtained. Then, an 11-week mathematical modeling teaching process was carried out in a learning environment prepared with mathematical modeling. It was revealed that the training carried out in a learning environment with today’s technology greatly improved the mathematical modeling competencies of mathematics teachers.